Synovitis, Acne, Pustulosis, Hyperostosis, and Osteitis (SAPHO) Syndrome with Cutis Verticis Gyrata: Case Report and Review of Literature - Wang Y; Wang S; Zheng L; Wang X; Wang H; Zhong Z; Liu S; Zheng X; Gao M (Dove Medical Press, 2022)
Yifan Wang,1- 3 Shan Wang,1- 3 Liyun Zheng,1- 3 Xiuli Wang,1- 3 Hui Wang,1- 3 Zhenyu Zhong,1- 3 Siqi Liu,1- 3 Xiaodong Zheng,1- 3 Min Gao1- 3 1Department of Dermatology, the First Affiliated Hospital of Anhui Medical University, Hefei, Anhui, People's Republic of China; 2Key Laboratory of Dermatology (Anhui Medical University), Ministry of Education, Hefei, Anhui, People's Republic of China; 3Inflammation and Immune Mediated Diseases Laboratory of Anhui Province, Hefei, People's Republic of ChinaCorrespondence: Min Gao; Xiaodong Zheng, Department of Dermatology, the First Affiliated Hospital of Anhui Medical University, No. 81 Meishan Road, Hefei, Anhui, 230032, People's Republic of China, Tel/Fax +86-0551-62923042, Email ahhngm@126.com; zhengxiaodong.1234@163.comAbstract: SAPHO (synovitis, acne, pustulosis, hyperostosis, and osteitis) syndrome is a rare disease clinically characterized by a wide range of cutaneous and osteoarticular manifestations. Here, we report a case of SAPHO syndrome with cutis verticis gyrata (CVG) and investigated the genetic causes in the four members of this pedigree. After failure of conventional treatments, a recombinant human TNF-α receptor II:IgG Fc fusion protein (rhTNFR:Fc, YISAIPU®) achieved good control of the disease at the 2-year follow-up. We did not identify any pathogenic mutation in this pedigree. We also summarized the clinical and therapeutic characteristics of 83 patients with SAPHO syndrome through the China National Knowledge Infrastructure (CKNI) database from 2016 to 2021. Patients with acne were young and predominantly male. About 45.8% patients were treated with biological therapies or traditional Chinese medicine (TCM), 84.2% of which showed positive effects against cutaneous and osteoarticular manifestations. We report a case of SAPHO syndrome with CVG that was successfully treated with rhTNFR:Fc. Our results reveal the genetic heterogeneity involved. Biologics and TCM are likely alternative options for the treatment of SAPHO syndrome.Keywords: cutis verticis gyrata, gene mutation, SAPHO syndrome, treatment, whole-exome sequencing